2014
DOI: 10.1002/ijc.28995
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the overall survival of patients with advanced-stage non-small cell lung cancer using data of routine laboratory tests

Abstract: Cancer patients undergo routine clinical monitoring with an array of blood tests that may carry long-term prognostic information. We aimed to develop a new prognostic model predicting survival for patients with advanced non-small cell lung cancer (NSCLC), based on laboratory tests commonly performed in clinical practice. A cohort of 1,161 stage IIIB or IV NSCLC patients was divided into training (n 5 773) and testing (n 5 388) cohorts. We analyzed the associations of 32 commonly tested laboratory variables wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…The identification of a prognostic index will help with appropriate treatment decisions, as well as enhance patient stratification in RCTs to achieve robust results. Several reports have demonstrated the feasibility and potential use of laboratory data in the stratification of patients in clinical trials [272829]. Our current study raises the importance of assessing novel tissue-based prognostic biomarkers for their discriminatory ability over and above the prognostic index identified here by easily obtainable clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 72%
“…The identification of a prognostic index will help with appropriate treatment decisions, as well as enhance patient stratification in RCTs to achieve robust results. Several reports have demonstrated the feasibility and potential use of laboratory data in the stratification of patients in clinical trials [272829]. Our current study raises the importance of assessing novel tissue-based prognostic biomarkers for their discriminatory ability over and above the prognostic index identified here by easily obtainable clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 72%
“…Few DSS have been developed in patient populations with mixed treatment options, but have not been externally validated, such as the Daniele score [ 63 ], Lin score [ 64 ] and Zhang score [ 65 ]. Only the Blanchon model [ 66 ] has been validated in another population [ 67 ], thereby, reaching Reilly level 2.…”
Section: Resultsmentioning
confidence: 99%
“…A study among patients with all stages of pancreatic cancer demonstrated that elevated BUN was associated with increased mortality in a final multivariable model, although not in the univariable analyses . Elevated BUN has also been associated with worse prognosis in patients with non‐small cell lung cancer, and advanced malignancies in patients receiving palliative care . In one study from Japan, a low BUN (<8 mg/dL) was found to be associated with higher 30‐day mortality after pancreatoduodenectomy, although indications for surgery in the study population included various cancers as well as nonmalignant lesions .…”
Section: Discussionmentioning
confidence: 99%